Book Review: Culture 2.0: The Intersection of National and Organizational Culture and Unruly Speech: Displacement and the Politics of Transgression - Milburn, Trudy (Management Communication Quarterly, 2024)
Keywords: book review; dept.aa

Sword with a dual edge: Membership categorization and stereotyping in elite European club football commentary (chapter 12) - Hansen, Alan; Milburn, Trudy (Communicated Stereotypes at Work, 2024)
Communicated Stereotypes at Work highlights the pervasiveness and complexity of stereotypes in the workplace by analyzing the role they play in a variety of professional settings. Contributors exp...
Keywords: dept.aa